Reducing Carbon Dioxide Emissions by Underground Storage in an Abandoned Coal Mine - an Initial Study - Chovanec, Josef; Závada, Jaroslav; Bouchal, Tomáš; Blažek, Vladislav; Ožana, Kamil (GeoScience Engineering, 2013)
This article is a basic study dealing with the issues of underground storage of carbon dioxide generated from different kinds of activities. Carbon dioxide can be stored underground as a free gas; gas dissolved in water, or can be adsorbed in the rock mass and in the remaining seams. The technology for processing and storage of carbon dioxide is known as carbon capture and storage (ccs). The article focuses on the possibility to store co2 underground at the paskov mine in the czech republic.